Comparative evaluation of cytotoxic and genotoxic effects of three resin-based sealers by 3,(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay and comet assay - an in vitro study - Vaidehi Vikas Dhopavkar; Sunita S Shivanand; Kishore Bhat; Anand C Patil; Preeti K Doddwad; Niraj Jayant Godbole (Wolters Kluwer Medknow Publications, 2021)
Background and Aim: The complete sealing of the pulpal space contributes to the better healing potential after an root canal treatment, and root canal sealers are an integral part of this treatment which comes in contact with the periodontal tissue. Biocompatibility of an endodontic sealer plays an important role in the root canal treatment procedure. Hence, the aim of the study was to compare and evaluate the cytotoxicity and genotoxicity effect of three resin-based sealers on human periodontal fibroblast cells. Settings and Design: This in vitro study was conducted in Dr. Prabhakar Kore's Basic Science and Research Center and K. L. E V. K. Institute of Dental Sciences, Belagavi. Materials and Methods: Human periodontal fibroblasts were incubated with 15 specimens of Group 1 - AH Plus Group 2 - MTA Fillapex, and Group 3 - GuttaFlow 2, respectively. Cytotoxicity was assessed by 3,(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay and genotoxicity was assessed by Comet assay at time intervals at 24 h and 48 h. Statistical Analysis: Data were analyzed by the Kruskal-Wallis and Mann-Whitney U-test. Results: AH Plus and GuttaFlow 2 did not show any cytotoxicity or genotoxicity. MTA Fillapex was slightly cytotoxic throughout the time interval, and it also showed low genotoxicity throughout the time periods for which it was tested. Conclusion: AH Plus and GuttaFlow 2 did not show any cytotoxic and genotoxic effect; however, MTA Fillapex showed cytotoxic and genotoxic effect throughout the time interval.